2021
DOI: 10.1002/2211-5463.13227
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effects of levosimendan on acute kidney injury following cardiac arrest via anti‐inflammation, anti‐apoptosis, and ERK activation

Abstract: Renoprotective effects of levosimendan on acute kidney injury following cardiac arrest via anti-inflammation, anti-apoptosis and ERK activation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…These are markedly augmented after ROSC in CA hospital patients and in an induced-CA rat model (26). Previous studies have also reported that BUN and creatine levels are increased at 1 day and 2 days after ROSC in an asphaxial CA rat model (31,32). Our experimental data were also similar to studies using a traditional I/R model.…”
Section: Discussionsupporting
confidence: 87%
“…These are markedly augmented after ROSC in CA hospital patients and in an induced-CA rat model (26). Previous studies have also reported that BUN and creatine levels are increased at 1 day and 2 days after ROSC in an asphaxial CA rat model (31,32). Our experimental data were also similar to studies using a traditional I/R model.…”
Section: Discussionsupporting
confidence: 87%
“…Levosimendan can effectively protect liver and kidney functions while preserving heart function, regardless of the presence of hepatic or renal impairment before it is used [23][24][25][26][27][28]. Partly of these protective effects due to their antiinflammatory and anti-apoptotic properties [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increasing success rate of ROSC, the incidence and mortality of post-resuscitation AKI remain significant ( 31 , 32 ). Some substances were proven to partly alleviate post-CPR AKI to some extent in animal model ( 33 , 34 ); however, there is insufficient evidence to demonstrate that their pharmacological effects can improve long-term survival. Therefore, there is an urgent need to explore novel and feasible therapeutic strategies to prevent AKI and improve outcomes after CPR.…”
Section: Discussionmentioning
confidence: 99%